The Effect of Good Corporate Governance on Firm Value - Imtizal Jauhara Kusuma; Dian Anita Nuswantara (Journal of Economics, Business, and Government Challenges, 2021)
This study aims to prove the effect of Good Corporate Governance (GCG) procedures which include the Board of Commissioners, Independent Commissioners, Audit Committee, Managerial Ownership and Institutional Ownership on Company Value. This research is a quantitative research because it aims to generalize the research results. The type of data used is secondary data with a research sample of non-financial state-owned companies that regularly publish financial reports on the Indonesian Stock Exchange during the period 2016 to 2018. Data analysis uses multiple linear regression using the SPSS program. The results of the analysis on the t test show that the variables of the Board of Commissioners and Institutional Ownership have an effect on firm value. While the three independent variables, the size of the Independent Commissioner, the Audit Committee and Managerial Ownership have no effect on firm value.